Knowledge Attitude and Practice among Health Care Professionals on COVID-19 Vaccine in Nepal: A Cross-sectional Online Survey - Shrestha, Bikal; Neopne, Arun; Shrestha, Sailendra KD; Parajuli, Roshan; Shrestha, Kundu; Buddhathoki, Pravash; Shah, Prajwal Bikram; Oli, Prakash Raj; Gyawali, Pratik; Shrestha, Dhan Bahadur (One Health Journal of Nepal, 2021)
Introduction: Vaccination is the most important preventive measure to control the outbreak of the COVID-19 pandemic throughout the world. Health care professionals face increased risk from exposure to COVID-19 in their work setting and thus, considered to be the primary recipients of vaccination. The main aim of this study was to gauge the Knowledge Attitude and Practice (KAP) about the planned vaccination campaign among health care workers in Nepal. Methods: A nationwide web-based cross-sectional survey was done regarding the knowledge, attitude, and practice of COVID-19 vaccination in Nepal among 270 health care workers from February to March 2021. Data from Google forms were exported in Excel-13. Cleaned data were analyzed using STATA v15. Results: A total of 270 health care professionals participated in the survey in which the mean KAP score was 12.75±2.85 with about 80% having fair KAP score about COVID-19 vaccines. There was a statistically significant association between chances of the score being poor to fair in KAP scoring with the level of education of participants, the occupation of the participants, and the first dose of vaccine receiving status. Conclusions: The majority of health care professionals in Nepal have higher acceptance and positive attitude and practice towards the COVID-19 vaccination. Lower level of education and health care workers other than the doctor, nurses, and paramedics had lower odds of fair KAP score regarding COVID-19 vaccination.